Ocular tropism of SARS-CoV-2 in animal models with retinal inflammation via neuronal invasion following intranasal inoculation - Gi Uk Jeong; Hyung-Jun Kwon; Wern Hann Ng; Xiang Liu; Hyun Woo Moon; Gun Young Yoon; Hye Jin Shin; In-Chul Lee; Zheng Lung Ling; Alanna G. Spiteri; Nicholas J. C. King; Adam Taylor; et al. (Nature Communications, 2022)
SARS-CoV-2 pathogenesis is very complex and not fully understood yet. Here, Jeong et al. show that intranasally infected K18-hACE2 transgenic mice develop ocular infection and retinal inflammation, while intratracheal infection results in the dissemination of SARS-CoV-2 from mouse lungs to their brain and eyes via unidirectional route and confirm the tissue tropism in Syrian hamster model.